Near-fatal cocaine intoxication in an infant with thrombotic microangiopathy associated with multiple organ failure - Alejandro Donoso Fuentes; Gianfranco Tomarelli Rubio; Camila Ampuero Acuña; Franco Díaz Rubio; Fernando Bracho Milic; Pamela Carrasco Troncoso (Sociedade de Pediatria de São Paulo, 2023)
ABSTRACT Objective: To report a pediatric case of drug-induced thrombotic microangiopathy caused by cocaine Case description: We report a nine-month-old patient who developed thrombotic microangiopathies after extreme cocaine intoxication, multiple organ dysfunction syndrome with hemodynamic dysfunction, anuric renal failure, liver failure, encephalopathy, and myocardial injury, corresponding phenotypically to thrombocytopenia-associated multiple organ failure. The patient received continuous venous hemofiltration and therapeutic plasma exchange, recovering satisfactorily. She was discharged after 30 days of hospitalization under the guidance of the childcare service, and was healthy after one year of follow-up. Toxicological samples confirmed high levels of cocaine and derivatives in blood, urine and hair. Comments: To our knowledge, this is the first reported pediatric case. There are particularities of cocaine intoxication pathophysiology that can trigger thrombotic microangiopathies because of vasoconstriction, direct endothelial injury, platelet activation, and increasing von Willebrand factor and fibrinogen levels. All of which results in a prothrombotic state, inflammatory dysregulation, and microvascular thrombi. The increasing use of cocaine, especially among young adults, puts children at high risk of toxicity, either by passive unintentional exposure, or abuse due to the increased availability in homes.